(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article analyzes the role of language clichés in the modern mass media discourse structuring. The language of media communication is interpreted in the context of global cliché system. The article describes structural types of clichés in the modern Ukrainian media texts.